Probing Cortical Sites of Antipsychotic Drug Action with in vivo Receptor Imaging - P. Shaw; L. S. Pilowsky (Behavioural Neurology)
Imaging receptors using radioactive ligands has allowed direct determination of the sites of action of antipsychotic drugs. Initial studies relating antipsychotic drug efficacy to action at striatal dopamine D2-like receptors have recently been undermined. Developments in imaging extrastriatal dopamine D2-like receptors suggest rather that antagonism of these receptors in the temporal cortex is the common site of action for antipsychotic drugs, with occupancy at striatal receptors relating more closely to extrapyramidal side effects. Further work into dopamine receptor subtypes and other receptor groups such as serotonin and GABA neurotransmitters awaits the development of suitable probes, but there are some initial finding. Again a main site of antipsychotic drug action is at cortical levels with high degrees of cortical D1 and 5HT2a receptor occupancy attained particularly by atypical antipsychotic drugs.